Nature of the miracle years : conservation in West Germany, 1945 - 1975 - Chaney, Sandra (Studies in German history, 2008)
After 1945, those responsible for conservation in Germany resumed their work with a relatively high degree of continuity as far as laws and personnel were concerned. Yet conservationists soon found they had little choice but to modernize their views and practices in the challenging postwar context. Forced to change by necessity, those involved in state-sponsored conservation institutionalized and professionalized their efforts, while several private groups became more confrontational in their message and tactics. Through their steady and often conservative presence within the mainstream of West German society, conservationists ensured that by 1970 the map of the country was dotted with hundreds of reserves, dozens of nature parks, and one national park. In doing so, they assured themselves a strong position to participate in, rather than be excluded from, the left-leaning environmental movement of the 1970s.